Polygenic risk score for defining personalized surveillance intervals after adenoma detection and removal at colonoscopy - Guo, Feng; Edelmann, Dominic; Cardoso, Rafael; Chen, Xuechen; Carr, Prudence R.; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann (Clinical gastroenterology and hepatology, 2023)
Background & Aims - Polygenic risk scores (PRSs) could help to define personalized colorectal cancer (CRC) screening strategies. The aim of this study was to evaluate whether a PRS, along with adenoma characteristics, could help to define more personalized and risk-adapted surveillance intervals. - Methods - In a population-based, case-control study from Germany, detailed information on previous colonoscopies and a PRS based on 140 CRC-related, single-nucleotide polymorphisms was obtained from 4696 CRC cases and 3709 controls. Participants were classified as having low, medium, or high genetic risk according to tertiles of PRSs among controls. We calculated the absolute risk of CRC based on the PRS and colonoscopy history and findings. - Results - We observed major variations of CRC risk according to the PRS, including among individuals with detection and removal of adenomas at colonoscopy. For instance, the estimated 10-year absolute risk of CRC for 50-year-old men and women with no polyps, for whom repeat screening colonoscopy is recommended after 10 years only, was 0.2%. Equivalent absolute risks were estimated for people with low-risk adenomas and low PRS. However, the same levels of absolute risk were reached within 3 to 5 years by those with low-risk adenomas and high PRS and with high-risk adenomas irrespective of the PRS. - Conclusions - Consideration of genetic predisposition to CRC risk, as determined by a PRS, could help to define personalized, risk-adapted surveillance intervals after detection and removal of adenomas at screening colonoscopy. However, whether the risk variation is strong enough to direct clinical risk stratification needs to be explored further.
Online verfügbar 21. März 2022, Artikelversion 20. Dezember 2022
Gesehen am 30.03.2023